Influence of gender and genetic polymorphism of natural killer cell genes on acute lymphoblastic leukaemia - Lee, Le Jie (2017)
Acute lymphoblastic leukaemia (ALL) is characterized by an over-proliferation of immature lymphoblasts in the bone marrow. It is the most common cancer in children but affects adults as well. The majority of ALL are B cell lineage however approximately 15% are of T-cell origin. ALL predominates among males, from 1.2 times in B-cell lineage to 2.2 in T-cell ALL. Natural killer (NK) cells are significant players of the innate immune response characterised by cytolytic activity against virus-infected and tumour cells. The role of NK cells in immune surveillance and the tumour microenvironment are supported by earlier studies. Furthermore, like ALL it appears to be increased in the male gender. The activity of NK cells is regulated by groups of inhibitory and activating receptors. The role of NK cells in the leukaemogenesis is still unclear.This study hypothesise that variation in NK cell associated genes may affect functional killing activities of NK cells and influence leukeamogenesis. The objective of this study is to investigate genetic polymorphisms and variations in NK cell associated genes in of ALL patients and contrast between sexes. The percentage of NK cells (CD56+) in peripheral blood mononuclear cells were compared between gender in B-cell and T-cell ALL and compared with healthy controls. The average percentage of NK cells in mononuclear cells was higher in male subjects including normal, B-ALL and T-ALL male compared to female subjects. Gene expression frequencies of activating and inhibitory killer cell immunoglobulin-like receptors (KIR), commonly studied were also compared between these samples. Significant absence in expression of KIR2DL1-L4, 3DL3, 2DS2 and S4 (p<0.04) were observed in ALL patients. The expression of KIR2DL1, 2DL3, 2DL4, 3DL3 and 2DS4 were significantly absent in T-ALL male patients when compared with normal male controls. Genetic mutation and polymorphism, particularly single nucleotide polymorphism (SNPs) and small variants were then examined for NK-related genes in ALL samples via next-generation sequencing (NGS). Significant small variants present in specific gender and groups were identified. The consequences of these small variants to amino acid coding were predicted. These small variants have potential effects to the NK cells of individuals. The effects of selected small variants identified by NGS on gene expression levels were also investigated using qPCR. Small variants present in KIR3DL2, KLRC1, KLRC2 and LILRB1 were found to be significantly associated with the downregulation of gene expressions. Gene copy number variations (CNVs) defined by deletion or amplification in NK cells associated genes were also identified following next-generation sequencing and further validated using real-time quantitative polymerase chain reaction (qPCR). In ALL patients, amplification was detected in LAIR2, KLRC1, NCR1, NCR3, KLRC2, KLRC3 and KLRC4 while deletion was detected in CD69 and KLRD1. Gene copy numbers of KLRC2 and KLRD1 were positively and significantly correlated with gene expression level. Lastly, the most common mechanism in epigenetic modification that is DNA methylation was investigated in the promoter regions of KIR. Hypermethylation or higher methylation index of KIR genes were observed in most ALL patients. Of these genes, KIR2DL4 showed significant negative correlation between methylation index and gene expression (rs= -0.610, p< 0.001). This study showed significant differences in genetics of NK cell related genes between ALL patients and healthy controls. There were also significant differences when genders were compared. These implied differences in function and activity of NK cells in the various groups and influence of gender from the variation in NK cell related genes may potentially affect leukaemogenesis on ALL. All the data from this fundamental study will lead to a better understanding on the innate immunity particularly the NK cell’s arm in ALL patients and normal individuals on gender basis. The new insight on the genetic polymorphism, gene copy number variation and DNA methylation in ALL may be used to associate ALL with leukaemogenesis for better diagnosis and therapy in future. This study showed influence of gender in terms of genetic polymorphism, DNA methylation and gene copy number variations on ALL.